Metabolically Active Human Brown Adipose Tissue Derived Stem Cells. (February 2014) - Silva, Francisco J; Holt, Dolly J; Vargas, Vanessa; Yockman, James; Boudina, Sihem; Atkinson, Donald; Grainger, David W.; Revelo, Monica P.; Sherman, Warren; Bull, David A.; Patel, Amit N.
Abstract Brown adipose tissue (BAT) plays a key role in the evolutionarily conserved mechanisms underlying energy homeostasis in mammals. It is characterized by fat vacuoles 5–10 µm in diameter and expression of uncoupling protein one, central to the regulation of thermogenesis. In the human newborn, BAT depots are typically grouped around the vasculature and solid organs. These depots maintain body temperature during cold exposure by warming the blood before its distribution to the periphery. They also ensure an optimal temperature for biochemical reactions within solid organs. BAT had been thought to involute throughout childhood and adolescence. Recent studies, however, have confirmed the presence of active BAT in adult humans with depots residing in cervical, supraclavicular, mediastinal, paravertebral, and suprarenal regions. While human pluripotent stem cells have been differentiated into functional brown adipocytes in vitro and brown adipocyte progenitor cells have been identified in murine skeletal muscle and white adipose tissue, multipotent metabolically active BAT‐derived stem cells from a single depot have not been identified in adult humans to date. Here, we demonstrate a clonogenic population of metabolically active BAT stem cells residing in adult humans that can: (a) be expanded in vitro; (b) exhibit multilineage differentiation potential; and (c) functionally differentiate into metabolically active brown adipocytes. Our study defines a new target stem cell population that can be activated to restore energy homeostasis in vivo for the treatment of obesity and related metabolic disorders. Stem Cells2014;32:572–581